Choice of Law and Recognition of Foreign Orders in the Administration of Estates in Malaysia - Halim, Akmal Hidayah; Arshad, Azhani (INSI Publications, 2012)
Administration of estates is not confined to only administering the deceased’s estate in a particular place or country. It covers the administration of the whole of his estates wherever situated. Generally, the lexsitus or the law of the place in which the property is situated governs the administration of immovable property while the law of the deceased’s domicile or lex domicilii for the movable property. In practice, an application for grant of representation will be made to the court of the deceased domiciled country for the purpose of administering the deceased’s estate. However where the deceased died leaving behindproperty situated in a foreign country, such grant will not suffice to administer the estate of the deceased person until it has been recognized by the court within the jurisdiction. In Malaysia,the High Court has an exclusive jurisdiction in the administration of the deceased’s estate especially in cases of choice of law and recognizing any foreign order in interjurisdictional cases of estate administration. Hence, this paper seeks to provide an overview of the administration of estates in Malaysia, its choice of law and further ascertain the extent to which the Malaysian courts will recognise and enforce the orders made by the courts of another. The law and procedure relating to the resealing of the foreign grant of representation or orders and the alternatives thereto are also propounded accordingly.